2001
DOI: 10.1046/j.1523-1755.2001.0590041374.x
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell chymase expression and mast cell phenotypes in human rejected kidneys

Abstract: These results show that increased expression of chymase in MCs is related to the severity of interstitial fibrosis in human rejected kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
74
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 30 publications
9
74
0
Order By: Relevance
“…In the ischemic kidneys of two-kidney, one-clip rats and in kidneys of subtotal nephrectomized rats, increases in chymase activity and expression are also observed (Sadjadi et al, 2005a). Clinical studies reported increased chymase expression in rejected kidneys (Yamada et al, 2001) and kidneys of patients with renovascular hypertension (Morikawa et al, 2005) and diabetes (Huang et al, 2003;Koka et al, 2006). Collectively, these data support the potential contribution of chymase-dependent intrarenal Ang II formation to the progression of renal injury.…”
Section: F Alternative Enzyme Pathwayssupporting
confidence: 55%
“…In the ischemic kidneys of two-kidney, one-clip rats and in kidneys of subtotal nephrectomized rats, increases in chymase activity and expression are also observed (Sadjadi et al, 2005a). Clinical studies reported increased chymase expression in rejected kidneys (Yamada et al, 2001) and kidneys of patients with renovascular hypertension (Morikawa et al, 2005) and diabetes (Huang et al, 2003;Koka et al, 2006). Collectively, these data support the potential contribution of chymase-dependent intrarenal Ang II formation to the progression of renal injury.…”
Section: F Alternative Enzyme Pathwayssupporting
confidence: 55%
“…This is in consonance with the phenotypic switch of MC T to MC TC and its association with allograft fibrosis that has been reported post-renal transplantation. 21,22 Nevertheless, whether MC TC phenotype is independently linked to development of CLAD, or more significantly, plays a pathologic role in CLAD remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that MCs contributed to renal diseases mainly through promotion of tubular interstitial injury [13,[15][16][17][32][33][34]. Most investigations focused on the roles of MCs on renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The MC T MCs are believed to be T cell-dependent and the MC TC MCs are believed to be T cell-independent [38]. In human renal tissue, different results have been reported on MC subtype [11,15,17,[32][33][34]. MC subtype is believed to be disease-dependent [16].…”
Section: Discussionmentioning
confidence: 99%